2016
DOI: 10.1136/gutjnl-2015-310784
|View full text |Cite
|
Sign up to set email alerts
|

Detection rate of serrated polyps and serrated polyposis syndrome in colorectal cancer screening cohorts: a European overview

Abstract: The detection rate of SPs is variable among screening cohorts, and standards for reporting, detection and histopathological assessment should be established. The median rate, as found in this study, may contribute to define uniform minimum standards for males and females between 50 and 75 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
102
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 48 publications
(35 reference statements)
12
102
1
Order By: Relevance
“…In our cohort, SPs were detected less frequently than in the primary colonoscopy screening cohort from the Netherlands and Poland,1 and we also observed a marked difference in SP detection rates between endoscopists which might have led to missed diagnosis of SPS. However, detection rates for proximal SPs and large SPs were comparable to the Polish cohort 1.…”
mentioning
confidence: 46%
See 2 more Smart Citations
“…In our cohort, SPs were detected less frequently than in the primary colonoscopy screening cohort from the Netherlands and Poland,1 and we also observed a marked difference in SP detection rates between endoscopists which might have led to missed diagnosis of SPS. However, detection rates for proximal SPs and large SPs were comparable to the Polish cohort 1.…”
mentioning
confidence: 46%
“…However, detection rates for proximal SPs and large SPs were comparable to the Polish cohort 1. It has been demonstrated that SPS is frequently unrecognised even in patients with large colorectal SPs which has been attributed to a failure in detecting SPs and not systematically applying WHO criteria 7…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…A guaiac faecal occult blood test cohort from the UK showed a frequency of SPS ranging from 0.03% to 0.66% 1 2. Other cohorts based on primary colonoscopy showed a prevalence of SPS between 0.1% and 0.4% 1.…”
mentioning
confidence: 97%
“…We read with interest the recent data reported by IJspeert et al ,1 Biswas et al 2 and Moreira et al 3 whom evaluated the prevalence of serrated polyposis syndrome (SPS), a disease characterised by the development of multiple serrated polyps throughout the colon with an increased risk to develop colorectal cancer (CRC),4 inside CRC screening programmes. A guaiac faecal occult blood test cohort from the UK showed a frequency of SPS ranging from 0.03% to 0.66% 1 2.…”
mentioning
confidence: 99%